Embodied metaphors in Friedrich Schiller's “Die Bürgschaft”: a cognitive-linguistic analysis - Demir, Kemal; Özenici, Salih (Frontiers in Language Sciences, 2026)
This article examines Friedrich Schiller's ballad Die Bürgschaft within the framework of Conceptual Metaphor Theory (CMT), focusing on the bodily grounding of metaphorical structures (embodiment). Based on a systematic stanza-by-stanza analysis of the ballad's 20 stanzas, it argues that recurrent embodied mappings play a central role in structuring abstract domains such as time, emotions, moral values, and decisive life events. Methodologically, the study identifies metaphorical expressions in each stanza, assigns source and target domains, and links these mappings to recurring image-schematic patterns. This procedure allows the analysis to move beyond isolated figures of speech and to reconstruct metaphorical language as a textually organized system that guides interpretation across the narrative progression. The results reveal four dominant, interacting patterns: TIME IS MOVEMENT (PATH-based urgency), EMOTIONS AS BODILY STATES, DIFFICULTY IS AN OBSTACLE (force–resistance dynamics), and MORAL APPROACHING (proximity/contact cues). Importantly, these mappings are treated as textually licensed and narratively functional configurations in a specific literary and cultural context, not as strong claims about universal embodiment. By situating the findings against recent cross-cultural and multimodal perspectives on embodied meaning, the paper positions literary analysis as a complementary, hypothesis-generating domain that can refine and contextualize empirically oriented research on embodiment, rather than replacing it.